Draft genome sequence of Komagataeibacter intermedius strain AF2, a producer of cellulose, isolated from Kombucha Tea - Corrêa dos Santos, Renato Augusto; Berretta, Andresa Aparecida; Barud, Hernane da Silva [UNESP]; Lima Ribeiro, Sidney José [UNESP]; González-García, Laura Natalia; Zucchi, Tiago Domingues; Goldman, Gustavo H.; Riaño-Pachón, Diego M. (American Society for Microbiology, 2015)
Here, we present the draft genome sequence of Komagataeibacter intermedius strain AF2, which was isolated from Kombucha tea and is capable of producing cellulose, although at lower levels compared to another bacterium from the same environment, K. rhaeticus strain AF1.